Molecular and Structural Insights into H2 Indicator Supraparticles: Lowering the Limit of Detection by Tuning Incorporated Catalyst Nanoparticles - Zhang, Kailun; Reichstein, Jakob; Groppe, Philipp; Schötz, Simon; Stockinger, Nina; Libuda, Jörg; Mandel, Karl; Wintzheimer, Susanne; Retzer, Tanja (Chemistry of Materials, 2023)
With the increasing interest in H2-based energy storage, H2 detectors gain significant importance. Here, we report on safe, i.e., spark-free, reliable, and highly reactive gasochromic H2 indicator supraparticles (SPs). They are assembled from different types of noble metal nanoparticles (NPs), SiO2 NPs, and the dye resazurin via spray-drying. Their sensing principle is based on the adsorption and activation of H2 on catalytically active noble metal NPs incorporated in the mesoporous supraparticulate framework. Upon stepwise hydrogenation of resazurin molecules with molecular mobility via activated H species, the indicator displays a fast color change visible to the naked eye. We investigate the effect of incorporating different catalytically active NPs into indicator SPs on their sensor performance at different H2 concentrations. We find that the size and material of the catalyst NPs have a strong influence on the sensor response of the H2 indicator as it changes the amount of activated H species available in the system. Enhancing the amount of interstitial H2O in the mesopores of the SPs increases their reaction volume but impairs the reproducibility of their sensor response. Among the studied materials, dispersed Pt NP-containing SPs give the overall best results in terms of overall performance toward H2 detection.<br